The Role of Cognitive Emotion Regulation in Drug-Seeking Behaviors in Students - Mansour Beyrami; Abbas Bakhshipour; Yousef Zohdi (Shiraz University of Medical Sciences, 2021)
Background: During adolescence, developmental changes related to pleasure structures in brain, and emotion dysregulation may lead to an increase of involvement in addictive behaviors. Thus, the present study aimed to examine the role of cognitive emotion regulation in drug-seeking behaviors in students. Methods: The present correlational study was conducted in 2021. The subjects included 320 students aged 13 to 17, who participated in this study after our announcement in schools of Tabriz city, Iran. We used the cognitive emotion regulation questionnaire and tendency to drug use scale for data collection. For data analysis, the correlations of the variables were primarily calculated via Pearson correlation method. Afterwards, we used the stepwise multiple regression analysis for prediction of dependent variable. Results: Acceptance strategy (coefficient= -0.124, P= 0.001), positive refocusing (coefficient= -0.133, P= 0.001), refocusing on planning (coefficient= -0.108, P= 0.02), positive reappraisal (coefficient= -0.589, P= 0.03), and putting into perspective (coefficient= -0.144, P = 0.001) could predict negatively the tendency to drug use in adolescents. Additionally, self-blame strategy (coefficient= 0.114, P= 0.002), other-blame (coefficient= 0.283, P= 0.001), rumination (coefficient= 0.142, P = 0.001), catastrophizing (coefficient= 0.180, P= 0.002) were found to be able to predict the tendency to drug use in adolescents. Conclusion: The obtained findings revealed that maladaptive cognitive emotional regulation strategies are associated with drug-seeking behaviors in students.